FUT2 genotype and secretory status are not associated with fecal microbial composition and inferred function in healthy subjects. (4th July 2018) - Turpin, Williams; Bedrani, Larbi; Espin-Garcia, Osvaldo; Xu, Wei; Silverberg, Mark S.; Smith, Michelle I.; Guttman, David S.; Griffiths, Anne; Moayyedi, Paul; Panaccione, Remo; Huynh, Hien; Steinhart, Hillary; et al.
ABSTRACT: Heritability analysis of the microbiota has demonstrated the importance of host genotype in defining the human microbiota. The alpha (1, 2)-fucosyltransferase 2 encoded by FUT2 is involved in the formation of the H antigen and the SNP, rs601338 is associated with ABO histo-blood group antigen secretion in the intestinal mucosa. Previous studies have provided non replicated results for the association of this polymorphism with the composition and inferred function of intestinal microbiota. We aimed to assess this relationship in a large cohort of 1, 190 healthy individuals. Genotyping was performed using the HumanCoreEXOME chip, microbial composition was addressed by 16S rRNA gene sequencing. Firmicutes, Bacteroidetes, and Actinobacteria were the dominant phyla in this cohort. Although we have sufficient power to detect significant associations of FUT2 genotype/ inferred phenotype with the microbiota, our data demonstrate that FUT2 genotype and secretor status is not associated with microbial alpha diversity, microbial composition or inferred microbial function after correction for multiple testing. Thus, FUT2 genotype and inferred phenotype are not associated with human fecal microbial composition and imputed function.